Molecular machinery providing copper bioavailability for spermatozoa along the epididymial tubule in mouse. Issue 6 (19th February 2019) - Ogórek, M; Herman, S; Pierzchała, O; Bednarz, A; Rajfur, Z; Baster, Z; Grzmil, P; Starzyński, R R; Szudzik, M; Jończy, A; Lipiński, P; Lenartowicz, M
Abstract: Progressive functional maturation of spermatozoa is completed during the transit of these cells through the epididymis, a tubule structure connecting a testicle to a vas deferens. Epididymal epithelial cells by means of their secretory and absorptive functions determine a highly specialized luminal microenvironment containing multiple organic and inorganic components. The latter include copper ions, which due to their redox properties are indispensable for critical homeostatic processes occurring in spermatozoa floating in different part of epididymis but can be potentially toxic. Main purpose of our study was to determine epididymal region-dependent expression and localization of copper transporters ensuring a tight control of copper concentration in epididymal fluid. We also aimed at identifying proteins responsible for copper uptake by spermatozoa and verifying whether this process is coordinated with copper supply to superoxide dismutase 1 (SOD1), a copper-dependent antioxidant enzyme. Our study identifies two ATPases—ATP7A, ATP7B and Slc31a1, major copper importers/exporters depending on their differential expression on epididymal polarized epithelial cells of the caput, corpus, and cauda. Next, ceruloplasmin seems to be a chief protein transporting copper in the epididymal fluid and providing this biometal to spermatozoa. The entry of copper to germ cells is mediated by Slc31a1 and is correlated with both expressions of copper chaperone for superoxide dismutase (CCS), copper chaperone directly providing copper ions to SOD1 and with the expression and activity of the latter. Our results outline a network of cooperating copper binding proteins expressed in epididymal epithelium and in spermatozoa that orchestrate bioavailability of this microelement for gametes and protect them against copper toxicity. Abstract : Epididymal expression of copper transporting proteins that contribute to the establishment of copper concentrations in luminal fluid in individual regions of epididymis and act in concert to provide copper to CCS-SOD1 complex in spermatozoa.